1990
DOI: 10.1002/ar.1092280412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal bilateral ureteral ligation on the development of the proximal tubule of the kidney in fetal rats: Morphometry and electron microscopic study

Abstract: Development of the proximal tubule in the fetal kidney was studied following ligation of both ureters of pregnant rats. The ligation was performed on days 15, 17, 19, and 21 of gestation and autopsy followed 24 hours after each operation. On fetal days 20 and 22, the proximal tubular length per unit volume (1 mm3) of whole kidney of the fetuses from the ligated mothers was significantly increased, while the ratio of total glomerular volume to total proximal tubular volume was remarkably decreased when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The differentiation of the glomerular membrane and maturation of the proximal tubule were accelerated by severe impairment of maternal renal function caused by bilateral ureteral ligation (18,19), and maternal unilateral nephrectomy increased the number and size of glomeruli in the offspring (20). We did not examine the fetal kidneys histologically, but even with our gross measures of renal weight and dimensions, we were able to demonstrate an abnormal growth pattern in the STNxF; i.e., their kidneys were wider than the kidneys of IntF so that their length-to-width ratio was reduced (Table 1).…”
Section: Fetal Renal Morphologymentioning
confidence: 99%
“…The differentiation of the glomerular membrane and maturation of the proximal tubule were accelerated by severe impairment of maternal renal function caused by bilateral ureteral ligation (18,19), and maternal unilateral nephrectomy increased the number and size of glomeruli in the offspring (20). We did not examine the fetal kidneys histologically, but even with our gross measures of renal weight and dimensions, we were able to demonstrate an abnormal growth pattern in the STNxF; i.e., their kidneys were wider than the kidneys of IntF so that their length-to-width ratio was reduced (Table 1).…”
Section: Fetal Renal Morphologymentioning
confidence: 99%
“…Fetal urine production is thereby stimulated by maternal ureteral ligation (Wells, 1946). We observed that in the kidney of fetuses of fetal days 20 and 22 from bilaterally ureter ligated mothers apical vacuoles in the proximal tubular cells are increased by the ligation (Okada & Morikawa, 1990). Furthermore, the surface area of the glomerular basement membrane and the length of the glomerular capillary per unit volume of glomerulus are increased (Okada & Morikawa, 1993) and shortening of the time for filtration of HRP through the glomerular basement membrane is observed in the fetuses from the ligated mothers (Okada et al, 1997).…”
Section: Effects Of Ligation Of Maternal Ureters On the Development Omentioning
confidence: 79%
“…x 26,500. , 1988) and the proximal tubules with relation to the glomerular functional development of kidney in fetal rats (Okada and Morikawa, 1990). Furthermore, the present results are supported by several lines of evidence concerning the onset of fetal kidney function in rats.…”
Section: Discussionmentioning
confidence: 99%